2019
DOI: 10.1021/acs.jpca.9b04611
|View full text |Cite
|
Sign up to set email alerts
|

Highly Accurate CCSDT(Q)/CBS Reaction Barrier Heights for a Diverse Set of Transition Structures: Basis Set Convergence and Cost-Effective Approaches for Estimating Post-CCSD(T) Contributions

Abstract: The ability to accurately calculate reaction barrier heights is of central importance to many areas of chemistry. We report an extensive study examining the basis set convergence of post-CCSD(T) contributions (up to CCSDT(Q)) for a diverse set of 28 reaction barrier heights. In contrast to previous studies, we focus here on larger transition structures (TSs) involving 4-7 non-hydrogen atoms. The set of reaction barrier heights includes pericyclic, bipolar cycloaddition, cycloreversion, and multiple proton tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 76 publications
4
63
0
Order By: Relevance
“…Thus, overall post-CCSD(T) contributions to reaction barrier heights normally do not exceed the 1 kJ mol -1 mark. A striking exception to this are the challenging cycloreversion fragmentation reactions for which the T-(T) and (Q) contributions reinforce each other, 131 and thus post-CCSD(T) contributions can reach up to 6.7 kJ mol -1 . Inspection of Table S2 of the Supporting Information reveals that post-CCSD(T) contributions to the reaction barrier heights in the Criegee22 database do not exceed the 1.5 kJ mol -1 mark and are therefore consistent with the general finding of ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, overall post-CCSD(T) contributions to reaction barrier heights normally do not exceed the 1 kJ mol -1 mark. A striking exception to this are the challenging cycloreversion fragmentation reactions for which the T-(T) and (Q) contributions reinforce each other, 131 and thus post-CCSD(T) contributions can reach up to 6.7 kJ mol -1 . Inspection of Table S2 of the Supporting Information reveals that post-CCSD(T) contributions to the reaction barrier heights in the Criegee22 database do not exceed the 1.5 kJ mol -1 mark and are therefore consistent with the general finding of ref.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study examined a set of CCSDT(Q)/CBS barrier heights for a diverse range of reactions, including pericyclic, bipolar cycloaddition, cycloreversion, and multiple-proton transfer reaction. 131 They found that CCSD(T)/CBS reaction barrier heights normally benefit from an effective error cancellation between the higher-order triples, T-(T), which tend to increase the barrier heights, and the quasiperturbative quadruples, (Q), which tend to reduce the barrier heights.…”
Section: Type Amentioning
confidence: 99%
“…The DBOC corrections ranged from −0.08 to −0.09 kcal mol −1 , showing no evidence of surface crossings. Based on the convergence of our methods we assume a conservative error from the ab initio limit of 0.25 kcal mol −1 [152–155] . The Gibbs Free energy correction was computed for each complex at 298.15 K using the harmonic frequency results.…”
Section: Resultsmentioning
confidence: 99%
“…Some small differences were noticed between the two sets of calculations. Results at the ccCA level of calculation were taken from the paper by Grimes et al [29], while the most recent results by Karton at the W3lite-F12 level were also considered [5,37].…”
Section: Computational Detailsmentioning
confidence: 99%
“…Since the barriers depend on the precise evaluation of both stable species (reactants and products) and transition states, normally very resource intensive methods are required to achieve high precision. CCSD(T) calculations [2][3][4] or beyond (including non-perturbative triple and quadruple excitations) are being presently employed in combination with very extensive basis sets (from quadruple up to sextuple zeta) extrapolated to the CBS limit, to obtain sub-kJ/mol precision [5]. But, of course, at an enormous computer cost.…”
Section: Introductionmentioning
confidence: 99%